Behavior of passive admixture in a vortical hydrodynamic field - Bobrov, R.O.; Kyrylyuk, A.V.; Zatovsky, A.V. (Condensed Matter Physics, 2006)
The motion of passive admixture of spherical particles in the stationary hydrodynamic field of a swirling flow is
studied. A spherical particle of a given mass in the hydrodynamic field of a swirling flow is located on a certain
circular orbit, where the centrifugal force is compensated by the radial drag force due to the sink. This leads
to the separation of the host fluid and admixture. A theory of Brownian motion of admixture in dilute solutions
with a non-uniform flow is constructed.